Traditional Worship as a Tool for Evangelism - Leonid МIKHOVICH (Богословські роздуми: Східноєвропейський журнал богословʼя)
The article discusses the evangelistic aspect of traditional worship in Russian-speaking Baptist churches in dialogue with the historical and religious context, with a special emphasis on the situation in Belarus. The first and second parts of the article highlight the importance of the evangelistic component of Baptist identity and provide examples to substantiate this statement. The author also analyzes the sources of the Baptist tradition of evangelism, including historical background and context-determined eschatological sentiments, as well as the personal conversion experiences of evangelicals. The third and fourth parts examine the tradition of evangelistic and "call" (invitation) services, analyze the components of traditional worship (worship space, prayer, singing, testimonies, preaching and a call to repentance) in terms of evangelism,and briefly attempt to explain the present weakening of an evangelistic emphasis and identify problems related to the evangelistic focus of worship, such as a simplified understanding of mission and a lack of attention to other aspects of worship.